IMPLEMENTASI PENGGUNAAN ANGGARAN PEMERINTAHAN TERHADAP SEKTOR PENANGANAN COVID-19 DAN KESEHATAN DI KOTA CIMAHI - Zuama, Agam; Aprillia, Arinda Bella (UPPM Politeknik TEDC Bandung, 2023)
The Cimahi City Government's handling of Covid-19 has received quite good criticism, in the field of budget use and matters related to government performance, the quality of government employee performance can be seen as a form of quality government performance results, and vice versa. This research was created as a public insight into the implementation of the budget that should be used to carry out work programs but also as funds for handling the Covid-19 outbreak. This research was carried out through a study of the Cimahi City Government Library. The method used in writing scientific papers uses a qualitative approach, by looking at the data and also the results that have been carried out before, coupled with the validity test taken as a reference in writing research. The results of this study indicate that the implementation of the budget as a fund for handling Covid-19 is going well and does not interfere with the technical work and public services carried out in the Cimahi City Government.